Measurement of Feynman- [chi] spectra of photons and neutrons in the very forward direction in deep-inelastic scattering at HERA - Andreev, Vladimir; Buniatyan, Armen; Huber, Florian; Povh, Bogdan; Sauter, Michel David; Schöning, André (The European physical journal. C, Particles and fields, 2014)
Measurements of normalised cross sections for the production of photons and neutrons at very small angles with respect to the proton beam direction in deep-inelastic $$ep$$epscattering at HERA are presented as a function of the Feynman variable $$x_F$$xFand of the centre-of-mass energy of the virtual photon-proton system $$W$$W. The data are taken with the H1 detector in the years 2006 and 2007 and correspond to an integrated luminosity of $$131~\text {pb}^{-1}$$131pb-1. The measurement is restricted to photons and neutrons in the pseudorapidity range $$η >7.9$$η>7.9and covers the range of negative four momentum transfer squared at the positron vertex $$6<Q^2<100$$6<Q2<100 GeV$$^2$$2, of inelasticity $$0.05<y<0.6$$0.05<y<0.6and of $$70<W<245~$$70<W<245GeV. To test the Feynman scaling hypothesis the $$W$$Wdependence of the $$x_F$$xFdependent cross sections is investigated. Predictions of deep-inelastic scattering models and of models for hadronic interactions of high energy cosmic rays are compared to the measured cross sections.
H1 Collaboration: V. Andreev, A. Baghdasaryan, K. Begzsuren, A. Belousov, P. Belov, V. Boudry, G. Brandt, M. Brinkmann, V. Brisson, D. Britzger, A. Buniatyan, A. Bylinkin, L. Bystritskaya, A.J. Campbell, K.B. Cantun Avila, F. Ceccopieri, K. Cerny, V. Chekelian, J.G. Contreras, J.B. Dainton, K. Daum, C. Diaconu, M. Dobre, V. Dodonov, A. Dossanov, G. Eckerlin, S. Egli, E. Elsen, L. Favart, A. Fedotov, J. Feltesse, J. Ferencei, M. Fleischer, A. Fomenko, E. Gabathuler, J. Gayler, S. Ghazaryan, A. Glazov, L. Goerlich, N. Gogitidze, M. Gouzevitch, C. Grab, A. Grebenyuk, T. Greenshaw, G. Grindhammer, D. Haidt, R.C.W. Henderson, M. Herbst, J. Hladkỳ, D. Hoffmann, R. Horisberger, T. Hreus, F. Huber, M. Jacquet, X. Janssen, H. Jung, M. Kapichine, C. Kiesling, M. Klein, C. Kleinwort, R. Kogler, P. Kostka, J. Kretzschmar, K. Krüger, M.P.J. Landon, W. Lange, P. Laycock, A. Lebedev, S. Levonian, K. Lipka, B. List, J. List, B. Lobodzinski, L. Lytkin, E. Malinovski, H.-U. Martyn, S.J. Maxfield, A. Mehta, A.B. Meyer, H. Meyer, J. Meyer, S. Mikocki, A. Morozov, K. Müller, Th. Naumann, P.R. Newman, C. Niebuhr, G. Nowak, K. Nowak, J.E. Olsson, D. Ozerov, P. Pahl, C. Pascaud, G.D. Patel, E. Perez, A. Petrukhin, I. Picuric, H. Pirumov, D. Pitzl, R. Plačakytė, B. Pokorny, R. Polifka, B. Povh, V. Radescu, N. Raicevic, T. Ravdandorj, P. Reimer, E. Rizvi, P. Robmann, R. Roosen, A. Rostovtsev, M. Rotaru, S. Rusakov, D. Šálek, D.P.C. Sankey, M. Sauter, E. Sauvan, S. Schmitt, L. Schoeffel, A. Schöning, H.-C. Schultz-Coulon, F. Sefkow, S. Shushkevich, Y. Soloviev, P. Sopicki, D. South, V. Spaskov, A. Specka, M. Steder, B. Stella, U. Straumann, T. Sykora, P.D. Thompson, D. Traynor, P. Truöl, I. Tsakov, B. Tseepeldorj, J. Turnau, A. Valkárová, C. Vallée, P. Van Mechelen, Y. Vazdik, D. Wegener, E. Wünsch, J. Žáček, Z. Zhang, R. Žlebčík, H. Zohrabyan, F. Zomer
Im Titel ist "chi" als griechischer Buchstabe dargestellt
Gesehen am 11.08.2020